The relationship between workplace spirituality and organizational citizenship behavior among health workers in christian-based hospitals: A quantitative correlational study - Chindie Mutiara Dihan; Tansri Adzlan Syah; Fatimah Zahra (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the relationship between workplace spirituality and organizational citizenship behavior (OCB) among healthcare professionals in Christian faith-based hospitals. A quantitative research design was employed using a total sampling technique involving 113 full-time employees. The workplace spirituality scale was developed based on Milliman’s conceptualization, encompassing three dimensions meaningful work, sense of community, and alignment with organizational values (α = 0.956). The OCB scale was constructed following Organ’s framework, consisting of five dimensions: altruism, conscientiousness, sportsmanship, courtesy, and civic virtue (α = 0.940). Pearson correlation analysis revealed a very strong and significant relationship between workplace spirituality and OCB (r = 0.961; p < 0.001). These findings indicate that workplace spirituality plays a critical role in enhancing organizational citizenship behavior among healthcare professionals.